Entrepreneurship as a job opportunity for women graduates in tourism - López-Gómez, Laura (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
In this paper we analyze the role of women as entrepreneurs in the tourism sector. The educational level of women who study tourism at university means that they have tools for entrepreneurship and that the university should encourage their entrepreneurial spirit as another employment opportunity. By carrying out a SWOT analysis, we detected that the current context is ideal for encouraging entrepreneurship among female graduates in tourism and we propose support tools from the universities where they were trained.